Relación entre la miopía y la sensibilidad al contraste en pacientes de 15 a 40 años que asisten a la óptica San Alejo, Los Ríos - Babahoyo, octubre 2018 – abril 2019 - Mosquera Bustamante, Manuel Jose (2019)
The investigation determined the relationship between myopia and contrast sensitivity in patients aged 15 to 40 years attending the San Alejo Optics, an observational analytical study was made, the descriptive method was used to study the variables, it was evidenced that 46% of the study population presented personal pathological problems, distance vision was examined with CSV tests following the ranges of 20 to 25 years, with the female sex being the most prevalent with 64%, 52% presented a degree of high myopia, in terms of the knowledge of myopia and its relationship with contrast sensitivity, 78% are unaware of their relationship and as it affects visual quality, 73% indicated that their vision worsens at night or in environments with low light, the diagnostic method was used, which helped with the evaluation procedure using the Pelli Robson test, this type of test significantly improved the contrast sensitivity in patients with Patients diagnosed with myopia and visual quality, 73% use mobile devices or computers frequently, this causes myopia to become a worrisome problem for visual health.